Associations Between Apolipoprotein-A5 Genotype, High-Fat Diet and Plasma Lipid Levels among HIV-infected Children Initiating Antiretroviral Therapy in India. (4th October 2017) - Srinivasan, Ramalingam; Karunaianantham, Ramesh; Chandrasekaran, Padmapriyadarsini; Gopalan, Bindu Parachalil; N, Sanjeeva G; Rajkumar, S; Kumar, S Ramesh; Swaminathan, Soumya; Shet, Anita
Abstract: Background: Both antiretroviral therapy (ART) and polymorphism in genes involved in lipoprotein metabolism contribute to the development of ART-induced dyslipidemia. Apolipoprotein A5 ( APOA5) gene variant, which vary by race/ethnicity, influence plasma lipid concentrations. We explored the association of candidate gene effect on plasma lipid levels with food in HIV-infected children initiating ART in south India. Methods: HIV-infected children, between 2 and 12 years of age initiating non-nucleoside reverse transcriptase inhibitor (NNRTI)-based ART during 2010–2014 were included. They were assessed for their dietary intake by 24-hour dietary recall. Fasting blood was drawn for serum triglycerides (TGL), total cholesterol and high-density cholesterol along with CD4 cell count, and HIV-1 viral load. APOA5 gene polymorphisms rs662799, rs3135506 were determined by Taqman single-nucleotide polymorphism (SNP) genotyping assays. The General Linear Model (GLM) was applied to explore the risk of hypertriglyceridemia for SNP's rs662799 and rs3135506 with food interaction in children. Results: Three hundred and ninety HIV-infected children median age (IQR): 9 (5–11) years; and median viral load: 141, 000 (25, 876–436, 000) copies/mL were started on NNRTI-based ART. The frequency of c allele was 20% and 3.0% in rs662799, rs3135506, respectively. The GLM model suggested that the SNP rs662799 has significant association with TGL( P < 0.01); there was, however no interaction between gene polymorphisms and food. Also, the prediction model revealed that those who had a carrier allele (C) had higher TGL level as compared with those with wild type (165 vs. 138 mg/dL) and girls had higher TGL levels compared with boys. Conclusion: Children with carrier allele of APOA5 are prone to hypertriglyceridemia, irrespective of diet or drugs. These children require periodic monitoring of lipid parameters and effective interventions to prevent the development of atherogenic or metabolic complications. Disclosures: All authors: No reported disclosures.